Pendekatan Partisipatif dalam Pemberdayaan UMKM: Studi Kasus Inovasi Jellybone dari Limbah Tulang Ikan - Hartoni, Hartoni; Sari, Dwi Inda; Melki, Melki; Ningsih, Ellis Nurjualisti; Febrianti, Amanda Astri Pratiwi; Isnaini, Isnaini; Pramudhya, Rizqy (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service program aims to empower MSMEs in Tanjung Batu Seberang Village, Ogan Ilir Regency, by utilizing fish bone waste into a high-value-added product called Jellybone. The approach used was Participatory Rural Appraisal (PRA) with an action research method over 1 months. The program included integrated training (production, business management, and marketing), application of appropriate technology, intensive mentoring, and institutional development. The results showed a significant increase in partners' capacity, with an average increase of 43.3% in understanding based on pre-test and post-test results. The establishment of the Joint Business Group (KUB)